1997
DOI: 10.1089/jir.1997.17.287
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction of HIV-1 Particle Release by Interferon-α Occurs Before Viral Protease Processing and Is Independent of Envelope Glycoprotein

Abstract: The effect of human interferon-alpha (Hu-IFN-alpha) on the maturation process of the human immunodeficiency virus type 1 (HIV-1) has been studied using stable cell lines that produce nonenveloped particles. These cell lines secrete particles devoid of the viral envelope proteins gp120 and gp41. The CH-1 cells produce active viral protease that correctly processes its natural substrates, whereas the CH-1kww cell line expresses an enzymatically inactive viral protease, thus producing immature viral capsids. A bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has been reported that IFN-I may produce a change in post-translation modifications of Gag proteins, as more basic forms of p55, p39 and p24 were detected in HIV-infected stable cell lines, which inhibit capsid polyprotein processing. In addition, particles remaining attached to the cell failed to mature into structures with condensed cores [8]. Other studies suggest that IFN-α blocks HIV-I release mediated by the ubiquitin ligase, ISG-15, one the IFN-induced proteins of the ubiquitin-like pathway.…”
Section: Effects Of Interferon On Retroviral Virogenesismentioning
confidence: 99%
“…It has been reported that IFN-I may produce a change in post-translation modifications of Gag proteins, as more basic forms of p55, p39 and p24 were detected in HIV-infected stable cell lines, which inhibit capsid polyprotein processing. In addition, particles remaining attached to the cell failed to mature into structures with condensed cores [8]. Other studies suggest that IFN-α blocks HIV-I release mediated by the ubiquitin ligase, ISG-15, one the IFN-induced proteins of the ubiquitin-like pathway.…”
Section: Effects Of Interferon On Retroviral Virogenesismentioning
confidence: 99%
“…Type I IFNs (a and b) suppress HIV replication at the levels of transcription initiation, 41 mRNA stability, 42 translation, 43 assembly and release of virions, 44,45 and reverse transcription. 46 The response to IFN also depends on the stage of infection as well as the cell type.…”
Section: Figmentioning
confidence: 99%
“…In studies utilizing several different viruses, infected cells treated with IFN produced viral particles with lower infectivity compared to untreated control cells [ 36 , 37 , 38 , 39 , 40 , 41 ]. To assess whether IFN plays a similar role in reducing WNV infectivity, we examined the effect of IFN-β neutralizing antibodies on the particle to PFU ratios of WNV-NY and WNV-AUS60.…”
Section: Resultsmentioning
confidence: 99%